2023
DOI: 10.1002/advs.202301567
|View full text |Cite
|
Sign up to set email alerts
|

Additively Manufactured Dual‐Faced Structured Fabric for Shape‐Adaptive Protection

Abstract: Fabric‐based materials have demonstrated promise for high‐performance wearable applications but are currently restricted by their deficient mechanical properties. Here, this work leverages the design freedom offered by additive manufacturing and a novel interlocking pattern to for the first time fabricate a dual‐faced chain mail structure consisting of 3D re‐entrant unit cells. The flexible structured fabric demonstrates high specific energy absorption and specific strength of up to 1530 J kg−1 and 5900 Nm kg−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…• Hydration drive programming (Zhang et al, 2018a;Li et al, 2021c) Stress-strain,Deformation, Stiffness Sundararaman et al, 2023;Tian et al, 2023;Wang et al, 2023), the construction of metamaterials is currently unable to reach the atomic or molecular scale. At present, most metamaterials are still large in scale and more like "building structures" and "products" and cannot be used as "materials" for the design and manufacture of various applications.…”
Section: Strain Typesmentioning
confidence: 99%
“…• Hydration drive programming (Zhang et al, 2018a;Li et al, 2021c) Stress-strain,Deformation, Stiffness Sundararaman et al, 2023;Tian et al, 2023;Wang et al, 2023), the construction of metamaterials is currently unable to reach the atomic or molecular scale. At present, most metamaterials are still large in scale and more like "building structures" and "products" and cannot be used as "materials" for the design and manufacture of various applications.…”
Section: Strain Typesmentioning
confidence: 99%
“…The emergence of this technology greatly reduces material waste in the manufacturing process and makes rapid manufacturing possible [ 9 ]. Moreover, it is a promising technology for manufacturing composite materials, which has the potential to free FRCs from the limitations of molds [ 10 , 11 ]. When producing porous structures using conventional composite materials, it is typically required to utilize compound molds.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that this requires a continuous power source, which is a drawback for wearable applications. Other research groups have shown that the fabric stiffness can be controlled using granular jamming, again requiring a power source (Wang et al, 2021;Hu et al, 2023;Tian et al, 2023;Xu et al, 2023). (Partik et al, 2023).…”
Section: Introductionmentioning
confidence: 99%